2019
DOI: 10.1111/1754-9485.12939
|View full text |Cite
|
Sign up to set email alerts
|

Faculty of Radiation Oncology 2018 workforce census

Abstract: Introduction This paper reports the key findings of the Faculty of Radiation Oncology 2018 workforce census and compares results with previous studies. Methods The census was conducted in mid‐2018 with distribution to all radiation oncologists and trainees listed on the college database in Australia, New Zealand, Singapore and overseas. There were new questions about hours spent on multidisciplinary meetings (MDTS), leadership positions held, management of inpatients, hypofractionation, stereotactic body radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 18 publications
0
28
1
Order By: Relevance
“…Both RO trainee and workforce demographics show improved female gender representation that reached gender parity in training programs and a 1.67:1 male-to-female ratio in the physician workforce. By comparison, the Australian RO workforce had a 1.67:1 male-to-female ratio in 2014, 15 whereas the 2017 ASTRO workforce study reported a rise in female representation from 25.8% in 2012 to 28.9% in 2017 (2.88:1 and 2.46:1 male-to-female ratios, respectively) in the United States RO workforce. 16 Men have traditionally outnumbered women in RO practice in Canada, but the gender gap has narrowed and is projected to reach parity sometime between 2030 and 2034.…”
Section: E Fmentioning
confidence: 92%
“…Both RO trainee and workforce demographics show improved female gender representation that reached gender parity in training programs and a 1.67:1 male-to-female ratio in the physician workforce. By comparison, the Australian RO workforce had a 1.67:1 male-to-female ratio in 2014, 15 whereas the 2017 ASTRO workforce study reported a rise in female representation from 25.8% in 2012 to 28.9% in 2017 (2.88:1 and 2.46:1 male-to-female ratios, respectively) in the United States RO workforce. 16 Men have traditionally outnumbered women in RO practice in Canada, but the gender gap has narrowed and is projected to reach parity sometime between 2030 and 2034.…”
Section: E Fmentioning
confidence: 92%
“…In the past, securing a specialist job was seen as a natural progression of training and may have been relatively seamless. However, in the last decade, there has been a steady and large increase in trainee numbers In Australia and New Zealand (ANZ) peaking at 159 in 2011 . This increase in trainee numbers has created apprehension about job prospects post training.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no ‘hard’ evidence to confirm whether trainees struggle to secure employment post training. In fact, the ‘evidence’ is either anecdotal or reflects apprehension amongst the radiation oncology community . Hence, an analysis of all recent graduates might provide some crucial information in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Many of the issues discussed in the United States have also been reported in Australia and New Zealand, so it would be instructive to highlight comparisons. [9][10][11][12][13] Perhaps more importantly, we might be able to learn from one another and facilitate changes.…”
mentioning
confidence: 99%
“…In fact, unemployment has remained between 1% and 3%. [11][12][13] We intend to regularly evaluate in detail our new graduate experiences to keep abreast of this situation. 9 Much has been written about the examinations.…”
mentioning
confidence: 99%